Kamusi ya tiba - Mwita, A. M. A.; Mwansoko, H. J. M., 1952- (Dar es Salaam : Taasisi ya Uchunguzi wa Kiswahili, Chuo Kikuu cha Dar es Salaam, 2003)
A dictionary of medical terms.
In Swahili.
Keywords: Medicine -- Dictionaries -- Swahili; English language -- Dictionaries -- Swahili